Efektivitas Media Video Animasi Islami terhadap Peningkatan Kemampuan Literasi dalam Pembelajaran PAI dan Budi Pekerti di Sekolah Dasar: The Effectiveness of Islamic Animated Video Media in Enhancing Literacy Skills in Islamic Education and Character Learning at Elementary Schools - Khodijatussoleha, Nuralpiyah; Komarudin, Komarudin; Hasanah, E.; Ismatullah, Ade; Malik, Muhammad Ibnu (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
Elementary school students’ literacy skills continue to face considerable challenges, particularly in Islamic Religious Education and Character Building (PAIBP), which requires understanding abstract moral and spiritual concepts. This study aims to examine the effectiveness of Islamic animated video media in enhancing the literacy skills of fifth-grade students at SDN 1 Cijengkol, Caringin District, Sukabumi Regency. Employing a quantitative approach with a survey design, this research involved the entire population of fifth-grade students (n=20) selected through a saturated sampling technique. Data were collected through structured questionnaires and interviews, then analyzed using simple linear regression. The findings reveal a significant influence of animated video media on students’ literacy abilities, indicated by a regression coefficient of 0.588 and an F-value of 25.84, exceeding the F-table value of 4.41. These results highlight that integrating animated video content into PAIBP instruction improves students' comprehension while fostering active engagement in learning. The study contributes to the growing literature on multimedia-based learning for character education in primary schools. Nevertheless, limitations such as a small sample size and a localized research setting must be acknowledged. Future research is encouraged to explore broader school contexts using experimental designs to evaluate the sustained impact of similar media interventions.